Physico-Mechanical Behavior of Room Temperature Vulcanized Maxillofacial Silicon after Addition of Glass Flakes - Ghassan Abdul-Hamid Naji 1*, Mohammed Moudhaffer Ali 2, Firas Abdulameer Farhan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The aim of this study was to assess the effect of glass flakes addition on some physical and mechanical properties of a maxillofacial silicone material. Material and method: A room temperature vulcanized (RTV) maxillofacial silicone (VST-50, Factor II Inc., USA) and Micronized glass flake, surface pre-treated with silane coupling agent (GF002, Glass flake Ltd, Leeds, UK) were used in this study. Two hundred (200) specimens were prepared and divided into five main groups based on the tests conducted (tear strength, tensile strength, elongation percentage, surface hardness and surface roughness). Then, each group was farther divided into four subgroups according to weight percentage of glass flakes as follow; control group (0%), other groups contain 0.5%, 1% and 1.5% of glass flake micro-particles (10 specimen from each group). Results: The collected data were analyzed with a one-way ANOVA and LSD multiple comparison test were utilized to show the differences among four studied groups. The 1% glass flakes-incorporated specimens exhibited the highest mean values of tear strength, tensile strength and elongation percentage. While, the highest mean values of hardness and roughness were obtained with 1.5% specimens.